2015
DOI: 10.1097/bpo.0000000000000419
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Apical Resection Following Growth-friendly Instrumentation in Myelomeningocele Patients With Gibbus

Abstract: Both the LT and the GR system are reasonable alternatives of fixation postkyphectomy, both of which preserve growth to differing degrees. In this patient population with an already severely stunted trunk height, the surgeon must choose whether the amount of extra growth achieved by the GR is worth the risk of an increased number of surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…Besides, for a child younger than 10 years, chosen vertebral column resection and long fusion are needed cautiously evaluate, in the risk of insufficient thoracic development. As a well-designed strategy, VCR following growth-friendly instrumentation in the younger patient was reported to preserve spinal growth [ 22 ]. Jeszenszky et al [ 23 ] performed PVCR in early-onset spinal deformities and advocated that additional surgical procedures are often necessary during growth, and hence, nonfusion instrumentation beyond the vertebral resection site is advantageous, as it permits spinal growth and the later addition of fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, for a child younger than 10 years, chosen vertebral column resection and long fusion are needed cautiously evaluate, in the risk of insufficient thoracic development. As a well-designed strategy, VCR following growth-friendly instrumentation in the younger patient was reported to preserve spinal growth [ 22 ]. Jeszenszky et al [ 23 ] performed PVCR in early-onset spinal deformities and advocated that additional surgical procedures are often necessary during growth, and hence, nonfusion instrumentation beyond the vertebral resection site is advantageous, as it permits spinal growth and the later addition of fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Выраженные вторичные изменения позвонков усложняют интерпретацию лучевых данных (КТ), в связи с чем для планирования операции рекомендуют применять 3D-модели позвоночника [12,19,20]. При этом кифэктомии с удалением от одного до пяти позвонков [21] и многоуровневой стабилизацией позвоночника [22] металлоконструкции [14,23] и переломами ее элементов [23], формированием псевдоартроза [24], дисфункцией имеющегося вентрикулоперитонеального шунта [22]. Значительную часть таких пациентов в дальнейшем оперируют неоднократно [14].…”
Section: Discussionunclassified
“…These authors showed a height of 1.05 cm per year between T1 and T12 in patients with growing rods and 0.84 cm per year between T1 and T12 who underwent the Luque technique. According to the study, the growing rod technique emphasized that this technique provides better lengthening than the Luque technique, but surgery should be performed every 6 months for lengthening [5]. In these patients, torocal stability was only achieved by placing pedicle screws at T2 and T3.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, complication rates in MMC patients have been reported as very high after kyphectomy. Whether a long segment fusion is performed or the growing rod lengthened, comparison of these techniques also results in 50% complications [5,22,23]. The most common complications were wound infections and implant failures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation